Liver Histogenesis in Chukar Partridge (Alectoris Chukar) Embryo - Shadi Hashemnia; Bahador Shojaei; Hamed Razavi (Negah Institute for Scientific Communication, 2015)
Introduction: In chick embryo, endodermal component of the liver becomes split into 2 diverticula in a short time. The anterior diverticulum lies to the left of the ductus venosus and the posterior one to its right side. As the liver primordium grows, it is invaded by the embryonic veins. Based on the different incubation time periods and evolutionary origin of avian species, various times for morphogenetic events of the liver are expected. The chukar partridge (Alectoris chukar) belongs to a common family with the chicken and shows 3 to 4 days longer embryonic period. This study was designed to describe normal histological and histochemical events of the liver histogenesis of the chukar partridge. It would be interesting to see how the time and sequence of developmental events of liver histogenesis are similar to those of the chick embryo. Methods: In this study, partridge (Alectoris chukar) embryos were studied from day 5 to 24 of incubation. In the course of the study, their liver 5-μm thick sagittal and transverse sections were prepared. Then, the sections were stained with hematoxylin-eosin (H&E) and Periodic Acid Schiff (PAS) methods and studied under the light microscope. Results: During the histogenetic study of the chukar partridge liver, we noted the structures and events such as the dark and light hepatocytes, mitotic divisions, sinusoids and kupffer cells, as well as the glycogen storage in the hepatocytes and their development, also changes due to the time of incubation period. Conclusion: Although the sequential events of the liver histogenesis of chukar partridge follow the general pattern of the other birds, some differences exist in the time of formation liver components compared to other studied species.